Visions of reconstruction 1940-1948 planning the engineered infrastructure for a post-war economy : windows on the view from Great George Street - Baldwin, Robert (Thomas Telford, 2005)
The ICE shows how innovative and comprehensive was the thinking carried out at Great George Street even as bombs fell around it. In a tightly confined circle round Great George Street (tight enough to be within the 400-yard radius of protective diversion of German bomb aiming that the electronic engineers had devised by 1941) some very important ideas were coordinated on the basis of well-informed engineering briefs.